Dark matter from electroweak single top production - Plehn, Tilman; Thompson, Jennifer M.; Westhoff, Susanne (Physical review, 2018)
Dark matter scenarios with spin-0 mediators in the s channel have be tested in well-established processes with missing energy, such as top-pair- and mono-jet-associated production. We suggest electroweak single top production in association with a dark matter pair as an alternative channel. Based on a realistic analysis for the LHC at 13 TeV, we demonstrate how to efficiently discriminate between the signal and standard model background using event kinematics. With 300 fb−1 (3 ab−1) of data, on-shell scalar mediators with a coupling strength gtS=1 to top quarks can be probed up to masses of 180(360) GeV. Single-top-associated dark matter production should thus be included as an independent search channel in the LHC dark matter program.